Determinants of Interprofessional Collaboration Among Nurses: The Role of Demographics, Work Experience, and Workplace Culture - Suharjo Suharjo; Harif Fadhillah; Eni Widiastuti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Interprofessional Collaboration (IPC) enhances the quality and safety of healthcare by integrating the expertise of multiple health professionals; however, its implementation in hospital settings is often hindered by barriers such as ineffective communication, unclear professional roles, hierarchical dominance, and unsupportive workplace culture. Objective: This study aimed to analyze the relationship between demographic characteristics, work experience, and workplace culture and the implementation of IPC among nurses. Methods: A cross-sectional quantitative study design was employed to examine the association between demographic factors, work experience, and work culture with IPC implementation among nurses at a general hospital in Banten Province, Indonesia. Eighty nurses were recruited using stratified random sampling. Data were collected through structured questionnaires and analyzed using descriptive and inferential statistics with SPSS version 27.0. Results: IPC implementation was significantly associated with age (p = 0.048), education level (p = 0.047), work experience (p < 0.001), and work culture (p < 0.001). Work culture emerged as the most influential factor, with an odds ratio (OR) of 7.429 (95% CI: 2.703–20.419). Conclusion: Both individual demographic factors and organizational context influence nurses’ IPC implementation, with workplace culture being the most influential factor, highlighting the need to foster a collaborative work environment through interprofessional communication training, inclusive decision-making, and supportive institutional policies.